Pengelolaan Sumber Daya Hutan Berbasis Kearifan Lokal Pada Masyarakat Bali - Fahyumi Rahman; Muzani Jalaludin (Jurnal Hutan dan Masyarakat, 2022)
The Forest resources have a roles and multi-function in supporting humans life. The Forest's management must be integrated with various stake holders, one of which is the locals community. The roles and function of the community is very important to maintaining the sustainability of forest functions. The tradition that grows in the community is a fundamental aspect in to designing forest management strategies based on local wisdom. The concrete step that needs to be taken is  the role of the community with the customary law that applies to the local community. The philosophyof tri hita karana  in Balinese society has a concept that can preserve forests in the midst of globalization and homogenization. Basically, the essence of the teachings of Tri Hita Karana emphasizes three human relationships in life in this world. The three relationships include relationships with fellow humans, relationships with the natural surroundings, and relationships with God that are interrelated with one another. The application of local wisdom in managing forests in an integrated manner has an influence on community behavior and the balance of forest functions. Thus, community empowerment in managing forests based on local wisdom based on the Tri Hita Karana's philosophy needs to be integrated into a structured and systematic management of mechanism to maintain, safeguard and the secure forest functions.